Maximum Likelihood Estimation in the Fractional Vasicek Model - Lohvinenko, Stanislav; Ralchenko, Kostiantyn (Lithuanian Journal of Statistics, 2017)
We consider the fractional Vasicek model of the form dXt = (α-βXt)dt +γdBHt , driven by fractional Brownian motion BH with Hurst parameter H ∈ (1/2,1). We construct the maximum likelihood estimators for unknown parameters α and β, and prove their consistency and asymptotic normality.
Keywords: fractional Brownian motion; fractional Vasicek model; maximum likelihood estimation; strong consistency; asymptotic normality